2018
DOI: 10.1016/j.bbmt.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' Tumor 1 Gene Expression Using a Standardized European LeukemiaNet-Certified Assay Compared to Other Methods for Detection of Minimal Residual Disease in Myelodysplastic Syndrome and Acute Myelogenous Leukemia after Allogeneic Blood Stem Cell Transplantation

Abstract: Overexpression of the Wilms' tumor 1 (WT1) gene is informative in many patients with acute myelogenous leukemia (AML) and myelodysplastic syndromes (MDS) and is measurable in peripheral blood (PB). Despite these advantages, WT1 has not broadly been established as a marker for minimal residual disease (MRD) monitoring after allogeneic hematopoietic stem cell transplantation (allo-HSCT) due to limited patient numbers, differing sample sources, and nonstandardized in-house methods. To estimate the value of WT1 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 32 publications
2
23
0
3
Order By: Relevance
“…Over the past several years other factors have been identified as important in prognosticating survival of patients with AML, such as molecular abnormalities and presence of minimal/measurable residual disease (MRD) before transplant [15][16][17][18][19]. Here we hypothesized that a prognostic model that includes molecular abnormalities and MRD would better stratify patients with AML undergoing AHCT and inform treatment decisions in the modern era.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years other factors have been identified as important in prognosticating survival of patients with AML, such as molecular abnormalities and presence of minimal/measurable residual disease (MRD) before transplant [15][16][17][18][19]. Here we hypothesized that a prognostic model that includes molecular abnormalities and MRD would better stratify patients with AML undergoing AHCT and inform treatment decisions in the modern era.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular relapse (M‐Rel) was defined by the recurrence of MDS‐ or AML‐specific disease markers such as chromosomal aberrations or chimeric fusion genes. If patients didn't have any disease specific markers, we defined the elevated levels of Wilms tumor 1 (WT1) in PB to over 100 copies/µgRNA as M‐Rel. Molecular complete response (MCR) was defined as WT1 <50 copies/µgRNA and disappearance of MDS‐ or AML‐specific disease markers.…”
Section: Methodsmentioning
confidence: 99%
“…WT1 expression analysis in MRD assessment is recommended by ELN using a standardized and certified ELN assay (59). Several reports showed that persistent high bone marrow or continuous increase in peripheral blood WT1 transcripts at 3 months post-transplant are associated with higher risk of relapse (60,61). Conversely, patients with sustained low WT1 levels after transplant have excellent outcomes (62).…”
Section: Mrd Assessmentmentioning
confidence: 99%